Pengaruh Inklusi Keuangan, Persepsi Risiko, dan Love of Money terhadap Minat Investasi pada Generasi Z dengan Kemajuan Teknologi sebagai Variabel Moderasi - Putu Serly Maharani; Putu Sri Arta Jaya Kusuma (Universitas Batanghari Jambi, 2026)
This study aims to identify the elements that influence Generation Z's investment interest in Bali. The main objective is to assess the influence of financial inclusion, risk perception, and love of money on Generation Z's investment interest, with technological advancement serving as a moderating variable. Using a quantitative research approach, this study employed purposive sampling and sample size determination based on the Lemeshow formula, resulting in a total of 326 respondents. Primary data were collected through online questionnaires distributed via Google Forms on social media platforms, and the data were analyzed using SEM-PLS. The findings indicate that financial inclusion has a significant positive influence on Generation Z's investment interest. Similarly, risk perception also explains a significant positive correlation with investment interest among this generation of Z. In addition, love of money is proven to have a significant positive effect on their investment interest. However, it should be noted that technological advancement significantly reduces the impact of financial inclusion on Generation Z's investment interest. Conversely, technological advancement does not significantly increase the relationship between risk perception and investment interest, but significantly strengthens the influence of love of money on investment interest in this generation of Z.